A decision support tool for planning biowaste management systems. (1st January 2020) - Delgado, Mónica; López, Ana; Cuartas, Miguel; Rico, Carlos; Lobo, Amaya
Abstract: Biowaste is one of the predominant fractions in municipal waste. Its easy degradation in the ground causes the emission of polluting gases and generates leachate, which pose a great environmental risk. Defining solutions for biowaste management may have a number of varied, sometimes opposing objectives, and involve several linked stages. This article presents a new tool for the planning of biowaste management systems. The tool distinguishes four stages within the waste management line: collection (defined by the separation model and the collection system), pre-treatment, treatment, and application. Several alternatives are considered for each stage. The different combinations of alternatives that define the management systems are evaluated in two phases. First, the compatibility matrix establishes the affinity between the alternatives selected for each stage and then each alternative is assessed using indicators associated with environmental, social, technical and economic criteria. Both management alternatives and criteria considered in the tool can be modified or extended according to the local circumstances. The paper describes a case study that shows the value of the tool as an aid in decision-making for alternative selection in waste management systems under different scenarios and priorities. Highlights: New tool for decision making in municipal biowaste management. Integrates economic, technical, social and environmental criteria. Despite its complexity, anaerobic digestion was the best-rated treatment. Door-to-door collection stands out for its environmental advantages. A case study shows tool adaptability to different scenarios.